FRAMING MEDIA ASING DAN PERAN OPINION LEADERS DALAM MEMBENTUK PERSEPSI TENTANG RESPONS KEBIJAKAN BANJIR DI ACEH - Ula, Khayranil; Darmadi, Darmadi; Saleh, Muhammad (Linimasa : Jurnal Ilmu Komunikasi, 2026)
Foreign media coverage of the Aceh flood crisis in November 2025 generated critical narratives regarding the Indonesian government’s disaster policy response. These narratives shaped not only international perceptions but also domestic public opinion through the mediation of opinion leaders. The objective of this article is to examine foreign media framing of the government’s response and to analyze the role of opinion leaders in interpreting and disseminating these frames within national public discourse. A qualitative approach was employed using Robert N. Entman’s framing analysis and the two-step flow of communication framework. Data were collected from foreign media reports published by Asia News Network, Lowy Institute, and The Straits Times, supported by official government documents as comparative data. The analysis focused on problem definition, causal interpretation, moral evaluation, and policy implications. The findings indicate that foreign media frame the Aceh flood as a humanitarian and structural crisis, while portraying government responses as slow and poorly coordinated. Opinion leaders play a significant role in reinforcing these frames in domestic discourse. These results highlight the importance of transparent, responsive, and structurally oriented disaster governance..